The Influence of Return on Equity and Debt to Asset Ratio on Financial Distress in Properties Subsector Companies and Registered Real Estate on the Indonesian Stock Exchange Period 2015-2023 - Ratna Dumilah (International Journal of Integrated Science and Technology, 2024)
This research aims to determine the effect of return on equity and debt to asset ratio on financial distress. The research method used is an associative descriptive method with a quantitative approach. The population in this research is the Properties and Real Estate subsector companies listed on the Indonesia Stock Exchange for the 2015-2023 period. The sample for this research was determined using a Purposive Sampling technique and obtained 4 companies in the Properties and Real Estate subsector with an observation period of nine years to obtain 36 sample data. Hypothesis testing in this research uses panel data regression analysis using the E-Views 12 program and the confidence level used is 5%. The results of this research show that simultaneously return on equity and debt to asset ratio have a significant effect on financial distress with a significance of 0.0000 < 0.05 and f-count > f-table (34.14013 > 3.327654499) and the coefficient of determination using Adjusted R-Squared is equal to 61.73% while the remaining 65.44% was influenced by other variables not examined in this research. Meanwhile, partially return on equity has a significant positive effect on financial distress with a significance of 0.0018 < 0.05 and t-count > t-table (3.387986 < 2.04227), debt to asset ratio has a significant negative effect on financial distress with a significance of 0.0004 < 0.05 and t-count > t-table (|-3.912824| > 2.04227).